(untitled) (Nonlinear Studies, 2018)
In this manuscript, we have a notion to implement Banach contraction principle along with the help of resolvent operator to analyze the existence of class of neutral fractional integro-differential systems (FNIDS) with state-dependent delay(SDD) in Banach spaces. An example to exemplify the concept is offered at the end.